2011
DOI: 10.2135/cropsci2010.07.0411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oleic Acid Content on Yield in Winter Oilseed Rape

Abstract: Winter oiiseed rape {Brassica napus L.) with a inigh oleic (>75%) and/or iow iinolenic acid (-2%) content in the seed oil is of interest for nutritional and teciinicai purposes. We anaiyzed whetiier a change in seed fatty acid composition has a direct infiuence on yieid. Parental lines with different fatty acid composition were crossed, the segregating F^ popuiations were divided, and F3 buiks with contrasting fatty acid profiles were tested in two experiments. In Experiment 1, we developed four buiks in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The content of the oleic acid in leaves can be used as a sensitive agronomic parameter for the prediction of the oleic acid spectra in rapeseed. This conclusion is similar to the research results of Schierholt et al [17] and Gao et al [18]; that is, in breeding, materials with a high oleic acid content in seeds can be predicted and screened by detecting the oleic acid content in vegetative organs. However, this study only discussed the effect of the most sensitive parameter as the intermediate variable in constructing the prediction model and did not consider the case in which multiple agronomic parameters were used to estimate the oleic acid content in rapeseed.…”
Section: Oleic Acid Content In Leaves Can Be Used As a Sensitive Para...supporting
confidence: 91%
See 1 more Smart Citation
“…The content of the oleic acid in leaves can be used as a sensitive agronomic parameter for the prediction of the oleic acid spectra in rapeseed. This conclusion is similar to the research results of Schierholt et al [17] and Gao et al [18]; that is, in breeding, materials with a high oleic acid content in seeds can be predicted and screened by detecting the oleic acid content in vegetative organs. However, this study only discussed the effect of the most sensitive parameter as the intermediate variable in constructing the prediction model and did not consider the case in which multiple agronomic parameters were used to estimate the oleic acid content in rapeseed.…”
Section: Oleic Acid Content In Leaves Can Be Used As a Sensitive Para...supporting
confidence: 91%
“…Two association analysis methods, grey correlation analysis (GRA) and Pearson correlation analysis, were used in this study. Among them, GRA, as a grey system analysis method, applies to the study of the strength relationship between dependent variables affected by other factors [17], that is, the degree of influence among various factors is determined by the correlation degree. It is mainly used to identify the optimal estimated agronomic parameters.…”
Section: Association Analysismentioning
confidence: 99%
“…For example, a FAD2 mutant in Arabidopsis failed to undergo normal growth during development at low temperatures ( Miquel et al, 1993 ; Miquel and Browse, 1994 ). Furthermore, another report suggested that high oleic acid expression in rapeseed would likely be accompanied with reduced yield and lower germination rates ( Schierholt and Becker, 2001 , 2011 ). Thus, although it was beyond the scope of the present study, a comprehensive exploration was required to evaluate the effects of increased oleic acid on the yield of N1379T.…”
Section: Discussionmentioning
confidence: 99%